Decarbonising Maritime Transport: The Role of Green Shipping Corridors in Making Sustainable Port‐City Ecosystems - Mina Akhavan (Ocean and Society)
Maritime transport plays a crucial role in global trade and tourism, yet it significantly contributes to global greenhouse gas emissions, posing environmental challenges that demand urgent solutions. This article explores the innovative concept of maritime green shipping corridors, an emerging strategy aimed at decarbonising the shipping industry. By analysing the origins of green corridors from urban and transportation perspectives, the article outlines their evolution towards multimodal, zero‐emission shipping solutions. It highlights the role of international frameworks, such as the International Maritime Organization Clydebank Declaration, in facilitating the transition to green shipping routes and the proliferation of zero‐carbon fuels. The article also assesses the integration of renewable energy technologies, alternative fuels, and electrification in port operations, as well as the broader spatial and economic impacts on port‐city ecosystems. With the potential to enhance urban sustainability, promote green logistics, and drive global decarbonisation efforts, maritime green shipping corridors represent a crucial framework for future research and policy development. However, the article highlights the need for further studies to evaluate the socio‐economic and environmental impacts on local communities and regional planning.